2014
DOI: 10.4236/health.2014.612183
|View full text |Cite
|
Sign up to set email alerts
|

Graves' Disease Thyroid Color-Flow Doppler Ultrasonography Assessment: Review Article

Abstract: Graves' disease, as known today, is an autoimmune, diffuse, chronic disease of thyroid gland, as described by Robert Graves in 1835. It presents genetic predisposition and unknown etiology evidence, which is influenced in its development by several factors, including environment (dietary iodine intake, stress, drugs and infections). The disease is characterized by one or more changes: hyperthyroidism, goiter, ophthalmopathy, skin changes and pretibial myxedema, around 5% less common, and other symptoms 90% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It was clearly observed that cent percent of Graves' disease patient had increased thyroid blood flow in comparison to subacute thyroiditis in which more than three quarters showed decreased flow. Cut off value of 30cm/sec was considered in differentiation between Graves' disease from thyroiditis based on a review of relevant literature [3,4]. Our findings were in agreement with the findings of those investigators revealing more than 90% of the Graves' patient above the mentioned cut off while 80% of subacute cases were below.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was clearly observed that cent percent of Graves' disease patient had increased thyroid blood flow in comparison to subacute thyroiditis in which more than three quarters showed decreased flow. Cut off value of 30cm/sec was considered in differentiation between Graves' disease from thyroiditis based on a review of relevant literature [3,4]. Our findings were in agreement with the findings of those investigators revealing more than 90% of the Graves' patient above the mentioned cut off while 80% of subacute cases were below.…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid blood flow was seen by color Doppler power mode. PSV of the inferior thyroid artery of >30cm/sec was considered significantly high and suggestive of Graves disease and <30cm/sec for thyroiditis [3]. RAIU was considered as the gold standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, surgeons performing USG examination will be an extension of clinical evaluation in the outpatient department with the results available immediately for choosing the management strategy. 7,8 Ralls et al 9 in 1987 used CD in Graves' patients to show the increased blood flow in the thyroid gland. They coined the term thyroid inferno, indicating diffuse increase in thyroid parenchyma vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, those features have been general findings for these diseases and are not helpful in the differential diagnosis. Detection of increased thyroid vascularity on the Doppler US examination is very significant for thyroid diseases (5). Thyroid parenchymal blood supply has been shown to increase, especially in Graves' disease and early stages of Hashimoto's thyroiditis.…”
Section: Introductionmentioning
confidence: 99%